EVOLUTION OF CONFLICT STUDIES IN THE INTERNATIONAL SECURITY CONTEXT IN POST-SOVIET RUSSIA - A. I. Nikitin (Vestnik MGIMO-Universiteta)
Article analyses formation and development of the conflict studies in Russia as a sub-discipline within political sciences, on the edge between political theory and studies of international relations and international security. Article defines stages of formation of conflict studies in Russia, analyzes social request for studies of conflicts, considers influence of foreign and international institutes and research, both form the CIS and from other foreign countries, onto the conflict studies in Russia. Author postulates turning of the "New Political Thinking"paradigm elaborated by Gorbachev that allowed reconsidering Moscow's attitude towards various conflicts and rethinking of theoretical principles of conflict analysis, that are not anymore limited to class struggle and ideological contradictions. Introduction of more pluralistic concepts of "socio-political model" and "world order" instead of Marxist category of "socio-economic formation" led to remodeling of international relations along new lines, as well as study contradictions within one social system. Splash of inter-ethnic and separatist conflicts in the first half of the 1990s led to shaping of "practically oriented conflict studies" reflecting political interests of conflict sides in conflicts in Karabakh, Georgia/Abkhazia, Georgia/South Ossetia, Moldova/Transnistria. On the eve of 1990s-2000s formation of theoretical systemic conflict studies as a discipline took place, and this discipline was already quite strongly interfaced with international and foreign conflict studies theory. Article considers role of various institutes of the Russian Academy of Science, research centers including Russian Council on International Affairs, Council on Foreign and Defense Policy? Russian Pugwash Committee, Center for Political and International studies, Moscow Carnegie Center, Russian institute for Strategic Studies, Institute for the USA and Canada Studies, etc. As a separate direction of studies article tackles studies of post-soviet conflicts by foreign institutes and centers, like UNIDIR (Geneva), SIPRI (Stockholm), EU ISS (Paris), British Royal institute of International Affairs. Interaction of Russian and Swiss scientists on the basis of Geneva-based GCSP and DCAF attracts special attention. In conclusion typical issues in focus, as well as theme fields of the Russian conflict studies as a sub-discipline within political sciences are formulated.